Investigations on the behavior of zinc and copper complexes containing polydentate amine ligands - Beitat, Alexander; Justus Liebig University Giessen (My University, 2012)
Copper and zinc complexes with dipicolylamine as binding motif attracted growing interest with regard to their extraordinary properties. There are examples of transition metal complexes using derivatised bispic compounds as ligands in many fields of chemical research. Hence studies on selected derivatives of bispic and their copper and zinc complexes were initialized and the results that could be achieved are presented in this work. Extending the bispic binding unit with a fourth nitrogen atom leads to a tripodal ligand class well known for their stabilization of reactive oxygen intermediates of copper coordination compounds and thus enabling studies on metalloenzymatic oxygenation reactions. Unspenp affords the opportunity to combine an extraordinary binding site for copper and zinc ions with additional functionalities. Coordination compounds using functionalized derivatives of unspenp as ligands are supposed to exhibit extraordinary properties with regard to studying and activating reactive oxygen intermediates of their copper(I) complexes. A minor part of this work focused on the synthesis and characterization of copper(I) complexes and their reactivity towards dioxygen of selected representatives of this ligand family.Yellow solutions of copper(I) complexes using xylyl-bridged unspenp units as ligands were prepared and the reactivity towards dioxygen was studied using low temperature stopped-flow techniques. Reactive superoxido- and peroxido species could be successfully identified. All discussed species are highly reactive, but unfortunately more detailed kinetic studies could not be performed so far. Furthermore, initial results concerning the reactivity of yellow solutions of the copper(I) complex of Hant-unspenp towards dioxygen were reported. Highly reactive oxygen adduct species could be successfully identified.Studies on the reactivity of copper(I) complexes of 1,3-tpbd towards oxygen using nitriles as solvent revealed a red (525 nm/propionitrile) intermediate that could unfortunately not be characterized so far. Novel copper(II) complexes using 1,3-tpbd were successfully synthesized and structurally characterized in order to tune the magnetic properties. The use of the tetradentate ligands arsenate; and phosphate; lead to the formation of uncommon tetranuclear coordination compounds with a mu4-XO4 (X = P, As) binding motif. Influencing the structure by introducing bulky organic residues or nitrate as an anion, lead to the formation of polymeric chains. The study of the magnetic properties of selected compounds showed weak antiferromagnetic coupling that is explainable through orbital considerations and structural knowledge of the possible pathways. The study demonstrates methods to increase the nuclearity and dimensionality of the presented compounds by varying the nature of the co-ligand and thus creating new possible pathways for magnetic coupling between copper(II) atoms in order to achieve stronger effects.The first copper(I) compounds using the ligands L1 and L2 could be successfully synthesized and structurally characterized. The isolelectronic zinc(II) ion forms monomeric, four or five coordinated species using the ligands L1, L2 and Mebispic. In methanol, as a protic, coordinating solvent, the only octahedral zinc(II) complex using L1 as ligand formed during this study. This structural knowledge supported the explanation of the unusual fluxional behavior of the zinc(II) complexes of L1. Detailed emission studies in aprotic solvents successfully demonstrated the dependence of the emission and the electronic and structural properties of the studied compounds. Additionally an interesting rotation mechanism is occurring in the coordination sphere of the zinc(II) complexes in solution that could be proved by detailed one and two dimensional variable temperature NMR studies. The derivatisation of ligand L2 in order to study coordination polymers of copper and zinc, lead to the synthesis and characterization of three new ligands: L3, L4 and L5. Copper(I) complexes with the ligands exhibit sluggish behavior towards dioxygen. One-dimensional coordination polymers of copper(I) using the ligands L3 and L4 could be structurally characterized. It was possible to structurally characterize cage like copper(I) dimers of L4 and L5 also obtained with L1 as ligand. The use of zinc did unexpectedly not lead to the formation of coordination compounds with L4. All attempts resulted in the formation of an octahedral complex ion, where one zinc(II) ion is solely coordinated by the nitrogen in 4-position of two different ligand molecules, and not as one would expect by the excellent bispic binding site. The combination of copper and zinc ions and L4 to form heterobimetallic coordination polymers only lead to the formation of the known homometallic species. In contrast, NMR studies in solution point to the formation of a polymeric species.

Kupfer- und Zink-Koordinationsverbindungen mit Bispicolylamin als Bindungsmotiv erwecken aufgrund ihrer außergewöhnlichen und vielfältigen Eigenschaften steigendes Interesse. Beispiele für Übergangsmetallkomplexe mit bispic Derivaten als Liganden finden sich in vielen Bereichen chemischer Forschung. Studien mit ausgewählten bispic Derivaten und deren Kupfer und Zink-Komplexen bilden die Grundlage der vorliegenden Arbeit.Eine Erweiterung der bispic Bindungseinheit um einen vierten Stickstoff Donor führt zu einer tripodalen Ligandenklasse, die für die Stabilisierung reaktiver Metall-Sauerstoff Intermediate bekannt ist. Unspenp als gut erforschter Ligand dieser Klasse ist leicht zu derivatisieren und eröffnet daher die Möglichkeit der Kombination der starken Bindungsaffinität zu Kupfer- und Zink-Ionen mit zusätzlichen Funktionalitäten. Ein Teil dieser Arbeit zeigt die Synthese und Charakterisierung von Kupfer(I)-Komplexen mit Vertretern der unspenp-Familie und deren Reaktivität gegenüber Sauerstoff.In der vorliegenden Arbeit konnten bisher unbekannte Komplexverbindungen synthetisiert und interessante Eigenschaften bezogen auf Magnetismus, Emissionsverhalten und die Bildung eindimensionaler Koordinationspolymere beschrieben werden.Gelbe Lösungen von Kupfer(I)-Komplexen mit xylylverbrückten unspenp Einheiten als Liganden konnten dargestellt und ihre Reaktivität gegenüber Sauerstoff mittels Tieftemperatur stopped-flow Techniken untersucht werden. Dabei wurden erfolgreich reaktive Superoxido- und Peroxido-Spezies identifiziert. Alle hier diskutierten Intermediate sind hoch reaktiv, was detailliertere kinetische Untersuchungen bis dato verhindert hat.Desweiteren konnten erste Ergebnisse zur Reaktivität von gelben Kupfer(I)-Hant-unspenp Lösungen gezeigt werden. Auch hier wurden hoch reaktive Sauerstoff Adduktkomplexe identifiziert.Studien zur Reaktivität der in Nitrilen gelösten Kupfer(I)-Komplexe des Liganden 1,3-tpbd gegenüber Sauerstoff zeigten das Auftreten eines roten, bisher nicht identifizierten Intermediates (525 nm/Propionitril).Um die magnetischen Eigenschaften der Verbindungen zu analysieren, konnten bis dahin unbekannte Kupfer(II)-1,3-tpbd-Komplexe synthetisiert und strukturell charakterisiert werden. Die Verwendung der tetradentaten Liganden Arsenat und Phosphat führten zur Bildung sehr ungewöhnlicher mu4-XO4 (X = P, As) Bindungsmotive. Die Beeinflussung der Struktur durch die Verwendung sterisch anspruchsvoller organischer Reste oder Nitrat als Anion führte zur Bildung von Polymerketten.Anhand theoretischer Orbitalbetrachtungen und der gewonnenen strukturellen Kenntnisse, erscheint eine schwach antiferromagnetische Kopplung möglich.Auch wenn die erwarteten magnetischen Kopplungen nicht beobachtet werden konnten, zeigt die Studie neue Wege zur Verringerung der Nuklerität und Dimensionalität der gezeigten Koordinationsverbindungen durch die Variation der co-Liganden auf. Diese führen zu möglichen neuen Pfaden um stärkere Effekte zur magnetischen Kopplung zweier Kupfer(II)atome zu erzielen.Es konnten die ersten Kupfer(I)-Komplexe der Liganden L1 und L2 erfolgreich synthetisiert und strukturell charakterisiert werden. Das isoelektronische Zink(II)-Ion bildet mit den Liganden L1, L2 und Mebispic monomere, vier- oder fünffach koordinierte Komplexverbindungen aus. Der einzige oktaedrische Zink(II)-Komplex dieser Studie konntemit dem Liganden L1 in Methanol als protischem, koordinierendem Lösungsmittel dargestellt werden.Detaillierte Studien zum Emissionsverhalten in aprotischen Lösungsmitteln konnten erfolgreich die Abhängigkeit der Emission von den elektronischen und strukturellen Eigenschaften der untersuchten Verbindungen zeigen.Zusätzlich konnte ein interessanter Rotationsmechanismus in der Koordinationssphäre der Zink(II)-Komplexe in Lösung gezeigt werden. Belegt werden konnte dieser Mechanismus durch umfangreiche ein- und zweidimensionale NMR-Studien.Die Derivatisierung des Liganden L2 zur Untersuchung von Koordinationspolymeren mit Kupfer und Zink, führten zur Synthese und Charakterisierung der bis dahin unbekannten Liganden L3, L4 und L5. Mit Kupferkomplexen der Liganden L3 und L4 konnten eindimensionale Koordinationspolymere strukturell charakterisiert werden. Es ist gelungen, käfigartige Kupfer(I) Dimere mit den Liganden L4 und L5 strukturell zu charakterisieren, die auch schon mit dem Liganden L1 nachgewiesen werden konnten.Die Verwendung von Zink als Zentralatom führte überraschenderweise zur Bildung eines oktaedrischen Komplexes in dem ein Zinkion lediglich durch die Stickstoffatome in 4-Position koordiniert ist und nicht über die affine bispic- Einheit.Die Kombination von Kupfer und Zink Ionen und L4 mit der Absicht heterobimetallische Koordinationspolymere zu erzeugen führte zur Bildung der bekannten homometallischen Spezies. Im Gegensatz dazu weisen NMR Studien in Lösung auf polymere Spezies hin in der alle Pyridin-Stickstoffe koordinieren.
Untersuchungen der Eigenschaften von Zink- und Kupferkomplexen mit polydentaten Aminverbindungen als Liganden
Keywords: Zinkkomplexe; Kupferkomplexe; Rotationsmechanismus; Emissionsverhalten; zinc complexes; copper complexes; rotation mechanism; emission behavior; ddc:540